Does the average drug exposure in pregnant women affect pregnancy outcome? A comparison of two approaches to estimate the baseline risks of adverse pregnancy outcome. (2nd February 2015) - Wacker, Evelin; Navarro, Ana; Meister, Reinhard; Padberg, Stephanie; Weber‐Schoendorfer, Corinna; Schaefer, Christof
Abstract: Purpose: The results of observational cohort studies on drug effects on pregnancy outcome may depend among others on suitable comparison cohorts. The aim of this investigation was to compare two distinct definitions of maternal exposure status for comparison cohorts. Methods: We performed an observational cohort study of prospectively ascertained pregnant women who spontaneously contacted the Teratology Information Service (TIS) Berlin for drug risk consultation. The only exclusion criteria were exposures to established teratogens and/or fetotoxicants. Pregnancy outcomes of 3250 women with this "average drug exposure" were compared with 546 non‐exposed or insignificantly exposed pregnancies. Results: Neither the rate of major birth defects (3.0%; aOR 1.62; 95% CI 0.8–3.3) nor the risk of spontaneous abortion (16.0%; aHR 1.20; 95% CI 0.8–1.7) was significantly increased after average drug exposure, whereas the rate of electively terminated pregnancies was higher (11.1%; aHR 2.05; 95% CI 1.2–3.4). There were no differences in the risk of preterm birth (9.9%; aOR 1.38; 95% CI 0.9–2.0) and infants' birth weight ( p = 0.60). Conclusions: This study does not provide evidence for an increased risk of adverse pregnancy outcome after average drug exposure during pregnancy. Therefore, comparison cohorts with average drug exposure are appropriate for studies on potential teratogens or fetotoxicants based on observational data collected by TIS. Copyright © 2015 John Wiley & Sons, Ltd.